A new genus and species of Ripipterygidae (Orthoptera: Tridactyloidea) from mid-Cretaceous Kachin amber, northern Myanmar. (April 2023) - Zhao, Jinyang; Xu, Chunpeng; Jarzembowski, Edmund A.; Fang, Yan; Xiao, Chuantao
Abstract: A new genus and species, Burmaripipteryx oblongus gen. et sp. nov., is described based on a well-preserved orthopteran insect from mid-Cretaceous Kachin amber. Uninflated mesotibia and unsegmented cerci assign it to the family Ripipterygidae (Orthoptera: Tridactyloidea). Burmaripipteryx gen. nov. differs from the other ripipterygid genera in the following characters: epiproct small covering very basal part of cerci; brachium very small, about 1/2 of cerci both in length and width; subgenital plate about 1/2 of cerci in length, with distinct long setae ventrally. As the oldest male mud cricket, the new find of Burmaripipteryx oblongus gen. et sp. nov. enriches the biodiversity of fossil Ripipterygidae.